Adsorbate doping of MoS2 and WSe2: the influence of Na and Co. (12th June 2017) - Komesu, Takashi; Le, Duy; Tanabe, Iori; Schwier, Eike F; Kojima, Yohei; Zheng, Mingtian; Taguchi, Kazuaki; Miyamoto, Koji; Okuda, Taichi; Iwasawa, Hideaki; Shimada, Kenya; Rahman, Talat S; et al.
Abstract: We have investigated the influence of metal adsorbates (sodium and cobalt) on the occupied and unoccupied electronic structure of MoS2 (0 0 0 1) and WSe2 (0 0 0 1), through a combination of both photoemission and inverse photoemission. The electronic structure is rigidly shifted in both the WSe2 and MoS2 systems, with either Na or Co adsorption, generally as predicted by accompanying density functional theory based calculations. Na adsorption is found to behave as an electron donor (n-type) in MoS2, while Co adsorption acts as an electron acceptor (p-type) in WSe2 . The n-type transition metal dichalcogenide (MoS2 ) is easily doped more n-type with Na deposition while the p-type transition metal dichalcogenide (WSe2 ) is easily doped more p-type with Co deposition. The binding energy shifts have some correlation with the work function differences between the metallic adlayer and the transition metal dichalcogenide substrate.